2003
DOI: 10.1128/jvi.77.15.8532-8540.2003
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Inhibits Gammaherpesvirus Lytic Replication

Abstract: Nasopharyngeal carcinoma, Kaposi's sarcoma, and B-cell lymphomas are human malignancies associated with gammaherpesvirus infections. Members of this virus family are characterized by their ability to establish latent infections in lymphocytes. The latent viral genome expresses very few gene products. The infected cells are therefore poorly recognized by the host immune system, allowing the virus to persist for long periods of time. We sought to identify the cell-specific factors that allow these viruses to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
210
5
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(238 citation statements)
references
References 48 publications
22
210
5
1
Order By: Relevance
“…Our results are apparently at odds with a recent study of Brown et al (2003), who in their reporter gene model demonstrated that overexpression of p65 represses the transactivation potential of ORF 50, a protein involved in the switch to lytic replication. They argue that high levels of NF-kB may activate a cellular protein that participates in the repression of gammaherpesvirusspecific gene expression, therefore inhibiting lytic replication.…”
Section: Hhv-8 From Bcbl-1 2nd4 Is Incapable Of Initiating De Novo Incontrasting
confidence: 57%
“…Our results are apparently at odds with a recent study of Brown et al (2003), who in their reporter gene model demonstrated that overexpression of p65 represses the transactivation potential of ORF 50, a protein involved in the switch to lytic replication. They argue that high levels of NF-kB may activate a cellular protein that participates in the repression of gammaherpesvirusspecific gene expression, therefore inhibiting lytic replication.…”
Section: Hhv-8 From Bcbl-1 2nd4 Is Incapable Of Initiating De Novo Incontrasting
confidence: 57%
“…Lastly, gammaherpesviruses establish latent infections in lymphocytes and are implicated in nasopharyngeal carcinoma, Kaposi's sarcoma and B-cell lymphomas. NF-kB was recently implicated in promoting latency in gammaherpesvirusinfected cells, as its overexpression in epithelial and fibroblast cells suppressed replication of murine herpesvirus 68 (MHV68) and blocked activation of lytic promoters from MHV68 and Kaposi's sarcoma-associated herpesvirus (KSHV) (Brown et al, 2003). In contrast, NF-kB inhibition in KSHV-infected cells led to lytic protein synthesis and virus reactivation.…”
Section: Implication Of Nf-kb In the Cell Response To Viral Infectionmentioning
confidence: 99%
“…43 Signals from CD40 and LMP-1 and activated NF-B are known to inhibit the entry into lytic cycle. 44,45 Since NF-B is constitutively activated in H/RS cells and in the HL-derived cell lines as well, 46 this may explain why lytic replication was not induced in the KMH2 EBV cells.…”
Section: Discussionmentioning
confidence: 99%